Stable Dissipative Soliton Generation From Yb-Doped Fiber Laser Modulated via Evanescent Field Interaction With Gold Nanorods - Shiyu Lu; Lin Du; Zhe Kang; Jie Li; Bin Huang; Guobao Jiang; Lili Miao; Guanshi Qin; Chujun Zhao; Shuangchun Wen (IEEE Photonics Journal)
We demonstrated the dissipative soliton generation from a passively mode-locked ytterbium-doped fiber laser operating at 1041 nm by using evanescent field interaction with gold nanorods (GNR) saturable absorber (SA) experimentally. The GNRs, which have broadband longitudinal surface plasmon resonance absorption from ∼800 to ∼1500 nm, are synthesized by a seed-mediated growth method, and then composited with a D-shaped fiber to form the GNRs SA. The GNRs SA shows a modulation depth of 9.7% and low saturation intensity of 0.302 MW/cm2 . With the proposed GNRs SA, a dissipative soliton fiber laser was achieved with pulse duration 162.3 ps, repetition rate of 6.649 MHz at 1041 nm for a pump power of 220 mW. In addition, the signal-to-noise ratio can reach ∼77 dB. The experimental result may make inroads for the nonlinear optical applications of the plasmonic nanomaterials.